2012
DOI: 10.1097/ta.0b013e31824473ce
|View full text |Cite
|
Sign up to set email alerts
|

Folded free vascularized fibular grafts for the treatment of subtrochanteric fractures complicated with segmental bone defects

Abstract: V, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Infection definition varies between the included studies and several different surgical techniques were used. Although we cannot give evidence to support this recommendation, most of the studies suggest a two step reconstruction as the standard approach to manage infected bone defects: an extensive debridement, followed by antibiotic treatment before graft surgery [16, 21, 26, 29, 31, 32, 36, 40, 43, 44]. Furthermore, some of the studies use PMMA as a local antibiotic delivery and/or due to its ability to induce a biological membrane at the defect site [21, 29, 3234, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Infection definition varies between the included studies and several different surgical techniques were used. Although we cannot give evidence to support this recommendation, most of the studies suggest a two step reconstruction as the standard approach to manage infected bone defects: an extensive debridement, followed by antibiotic treatment before graft surgery [16, 21, 26, 29, 31, 32, 36, 40, 43, 44]. Furthermore, some of the studies use PMMA as a local antibiotic delivery and/or due to its ability to induce a biological membrane at the defect site [21, 29, 3234, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, the fibula was cut into segments and folded to fit the bony cavity (Fig. 2) [10,11]. Under microscope, one artery and two veins of the free fibular were anastomosed to the dissected vessels in the host site with 10-0 microsurgical stitches, reinstituting both arterial inflow and venous outflow to the fibular graft.…”
Section: Methodsmentioning
confidence: 99%
“…Since Taylor GI et al [9]. Firstly used vascularized fibular graft to reconstruct a large defect in a tibia in 1975, free vascularized fibular graft has been widely accepted for the reconstruction of long bone defect, especially when the defect is greater than 6cm [10,11]. Malizos KN et al stated that free vascularized fibular graft is also indicated if the blood supply of lesion site is deficient [39].…”
Section: Table1.clinical Details Of Patientsmentioning
confidence: 99%
“…Despite the absence of a universal treatment protocol, there has been a marked improvement in the knowledge and management of ONFHN in the most recent decades due to the accumulation of further research on the multiple treatment methods. [1][2][3][4]6,[8][9][10][11][12][13][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][33][34][35][36][37][39][40][41][42][43]51 The treatment options for patients are categorized as surgical and nonsurgical interventions. The nonsurgical treatments include restricted weight bearing protocols and pain management, while the surgical options include core decompression (CD) and osteotomy, nonvascularized structural grafts, electrical stimulation, vascularized bone grafts, and THR or total hip arthroplasty (THA).…”
mentioning
confidence: 99%
“…1,9,17,21,23,24,32,34,41,43,47,48,54 Free vascularized fibular flaps (FVFFs) have been studied in the most recent decade and have shown to be associated with low rates of conversion to THR and increases in HHS, an indicator of functionality, symptoms, and range of motion. [1][2][3][4][5][6][7][8][9][10][11][12][15][16][17][18][19][20]22,23,[25][26][27][28][31][32][33][34][35][36]38,[40][41][42]45,46,49,50,…”
mentioning
confidence: 99%